2012
DOI: 10.1128/jcm.01993-12
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxigenic Vibrio parahaemolyticus Strains Causing Acute Gastroenteritis

Abstract: We investigated the virulence properties of four Vibrio parahaemolyticus strains causing acute gastroenteritis following consumption of indigenous mussels in Italy. The isolated strains were cytotoxic and adhesive but, surprisingly, lacked tdh, trh, and type three secretion system 2 (T3SS2) genes. We emphasize that nontoxigenic V. parahaemolyticus can induce acute gastroenteritis, highlighting the need for more investigation of the pathogenicity of this microorganism. Vibrio parahaemolyticus infections cause a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…The test result supported that FORC_014 strain has pathogenesis activity. Based on these results, we suggest that FORC_014 is pathogenic, even though it is tdh and trh negative [5, 6, 27, 28]. …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The test result supported that FORC_014 strain has pathogenesis activity. Based on these results, we suggest that FORC_014 is pathogenic, even though it is tdh and trh negative [5, 6, 27, 28]. …”
Section: Resultsmentioning
confidence: 98%
“…While environmental strains rarely contain pathogenic genes thermostable direct hemolysin ( tdh ) and thermostable direct hemolysin-related hemolysin ( trh ), clinical strains which create foodborne illness, possess virulence factor including tdh , and trh . Therefore, tdh , and trh have been considered as the indicators of V. parahaemolyticus pathogenicity, which has an enterotoxic effect on the intestinal cells of the affected mammal [4, 5]. Recent studies, however, announced that some clinical strains identified negative for tdh and trh genes [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent evidence suggests that there may be additional factors responsible for differential virulence of this organism (10,11), the tdh and trh genes remain the most reliable indicators of virulence currently available. Therefore, understanding the growth and survival of strains carrying these genes, in addition to total V. parahaemolyticus populations, is important for evaluating the potential risk of illness from shellfish consumption.…”
mentioning
confidence: 99%